2016
DOI: 10.5433/1679-0359.2016v37n6p4285
|View full text |Cite
|
Sign up to set email alerts
|

Phytase and protease supplementation for laying hens in peak egg production

Abstract: The effects of enzyme combinations in diets for commercial laying hens need further clarification. The goal of this study was to determine if the type of protease used in diets supplemented with phytase affects performance, nutrient intake, egg quality or intestinal mucosa morphometry of laying hens during peak egg production. Seven hundred and eighty hens (25-week-old Hy-Line W36 hens) were assigned to a completely randomized design composed of five treatments/diets with 12 replicates of 13 birds each. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
3
6
1
Order By: Relevance
“…However, the addition of protease B in the diet provided an increase in this variable. These results are similar to those presented by Vieira et al (2016), who also observed a reduction in egg weight values of light laying hens at peak production fed a diet with reduced energy, protein, and amino acids. The authors found that the addition of the enzyme (Streptomyces fradiae, 0.125 g kg −1 in the feed) to the hens' diet promoted an increase in egg weight.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the addition of protease B in the diet provided an increase in this variable. These results are similar to those presented by Vieira et al (2016), who also observed a reduction in egg weight values of light laying hens at peak production fed a diet with reduced energy, protein, and amino acids. The authors found that the addition of the enzyme (Streptomyces fradiae, 0.125 g kg −1 in the feed) to the hens' diet promoted an increase in egg weight.…”
Section: Discussionsupporting
confidence: 91%
“…However, Lima et al (2012) did not observe any significant treatment effect on the egg mass when providing diets with low levels of crude protein (0.0 and 4.0 g/kg) with or without supplementation of enzymatic complex for light laying hens at 30 weeks old. Similar results were also found by Vieira et al (2016), who did not observe any significant differences in egg production of light laying hens at peak production fed diets with reduced energy, proteins, and amino acids, with or without the inclusion of proteases (Streptomyces fradiae, 0.125 g kg −1 in the diet and Bacillus licheniformis, 0.250 g kg −1 in the diet) in their composition. Considering that the reduction in the crude protein level of the diet can cause reduction in egg mass values of light laying hens (Silva et al, 2010;Mousavi et al, 2013), it can be inferred that the nutritional reduction of diets negative control A and B promoted reduction in the egg mass values found in the present research, since they had lower levels of crude protein and amino acids in their compositions.…”
Section: Discussionsupporting
confidence: 87%
“…It is seen that the literature on the effect of enzyme addition to laying hens diets on egg production is incompatible. In related studies [12,13,19,20] reported that the enzyme addition did not change egg production. On the other hand, Khan et al [21] reported that dietary enzymes increased egg production in laying hens.…”
Section: Resultsmentioning
confidence: 96%
“…Some researchers [15,16,17] reported that the addition of multi-enzyme improved the feed conversion rate in laying hens. In contrast, some researchers found the opposite results [18,19,20]. As it is known, 'FCR' is the ratio of feed intake to egg weight in laying hens.…”
Section: Resultsmentioning
confidence: 99%
“…Balancing the contents of protein, amino acids, minerals and vitamins is essential for high productivity in this category of birds. The feed mixture for laying hens is based on grain containing an increased amount of poorly digestible phytates, which accommodate up to 80% of the total phosphorus content in the grain (Vieira et al, 2016).…”
Section: Introductionmentioning
confidence: 99%